Assessment of land use/land cover change in Hadaf watershed using different transformation methods employing remote sensing, GIS and HEC-HMS modelling technique - PAMPANIYA, NIRAVKUMAR K.; TIWARI, MUKESH K. (Journal of Soil and Water Conservation, 2020)
The present study was undertaken to assess the effect of land use and land cover (LULC) change and different transformation methods on runoff generation in Hadaf watershed, Pachmahals district, Gujarat. The prominent hydrologic HEC-HMS model available with different loss, transformation and routing methods was applied to understand the rainfall to runoff transformation and its major influence by LULC and transformation methods. It was found that Clark UH method produced better prediction than SCS-UH transformation method in rainfall-runoff simulation. The parameter optimization significantly improved outcome, however, land use change significantly influence the rainfall-runoff transformation.